(untitled) (Nordic Journal of Practical Theology, 2024)
This article focuses on the local parish as a practical-theological resource in relation to the acute climate crisis and crisis for biological diversity. The author argues that theologizing grown out of local experiences has special strengths compared to statements developed on national levels of the church. This has to do with how local parish life is rooted in local circumstances, human lives as well as the richness of other forms of local biological life which makes parish life possible. The source of the argument comes from experiences in a local parish on the Swedish East Coast, where the extreme draught in the summer of 2018 gave rise to a continued engagement, which has contributed to theological changes. The understanding of the parish has been widened to include human and non-human creatures alike, which in turn is affecting patterns of praying, from praying for, to praying with the whole creation, of which humans are a part.